Β‐amyloid context intensifies vascular smooth muscle cells induced inflammatory response and de‐differentiation. Issue 3 (1st April 2013) - Vromman, Amélie; Trabelsi, Nesrine; Rouxel, Clotilde; Béréziat, Gilbert; Limon, Isabelle; Blaise, Régis
Summary: Several studies have shown that the accumulation of β‐amyloid peptides in the brain parenchyma or vessel wall generates an inflammatory environment. Some even suggest that there is a cause‐and‐effect relationship between inflammation and the development of Alzheimer's disease and/or cerebral amyloid angiopathy (CAA). Here, we studied the ability of wild‐type Aβ1‐40 ‐peptide (the main amyloid peptide that accumulates in the vessel wall in sporadic forms of CAA) to modulate the phenotypic transition of vascular smooth muscle cells (VSMCs) toward an inflammatory/de‐differentiated state. We found that Aβ1‐40 ‐peptide alone neither induces an inflammatory response, nor decreases the expression of contractile markers; however, the inflammatory response of VSMCs exposed to Aβ1‐40 ‐peptide prior to the addition of the pro‐inflammatory cytokine IL‐1β is greatly intensified compared with IL‐1β‐treated VSMCs previously un‐exposed to Aβ1‐40 ‐peptide. Similar conclusions could be drawn when tracking the decline of contractile markers. Furthermore, we found that the mechanism of this potentiation highly depends on an Aβ1‐40 preactivation of the PI3 Kinase and possibly NFκB pathway; indeed, blocking the activation of these pathways during Aβ1‐40 ‐peptide treatment completely suppressed the observed potentiation. Finally, strengthening the possible in vivo relevance of our findings, we evidenced that endothelial cells exposed to Aβ1‐40 ‐peptide generate an inflammatory context and have similar effects than the ones described with IL‐1β. These results reinforce the idea that intraparietal amyloid deposits triggering adhesion molecules in endothelial cells, contribute to the transition of VSMCs to an inflammatory/de‐differentiated phenotype. Therefore, we suggest that acute inflammatory episodes may increase vascular alterations and contribute to the ontogenesis of CAA.